DESIGN OF WEB-BASED ELECTRONIC GOODS CREDIT APPLICATION USING FAST METHOD (CASE STUDY: QORETWODUO STORE) - Nabila, Sabina; Zakir, Ahmad; Dewi, Arie Rafika (Cattleya Darmaya Fortuna, 2025)
The QoreTwoDuo shop is a business sector that sells and buys electronic goods such as household appliances to personal computers and laptops. The QoreTwoDuo shop also accepts applications for credit for electronic goods to customers. The QoreTwoDuo electronics shop does not yet have an application that can help provide information about electronic products that are bought and sold and goods that can be credited at the shop to the wider community, for potential customers who have low incomes to buy these products for their household needs is very difficult, because Electronic goods are very expensive when bought with cash. A customer data processing system is very necessary to send data on customers who have made credit payments and have not paid their monthly credit installments, so that qoretwoduo shop owners can find out which customers are paying on time and who are late paying their credit. A customer data processing system is very necessary to send data on customers who have made credit payments and have not paid their monthly credit installments, so that qoretwoduo shop owners can find out which customers are paying on time and who are late paying their credit. So that shop owners can find out the financial reports that come in every month using the FAST method which functions in developing systems that can produce high quality systems in a short time.